2003
DOI: 10.1007/s11743-003-0262-5
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion formation and detergency with oily soils: I. Phase behavior and interfacial tension

Abstract: The ultimate objective of the project was to investigate the relationship between microemulsion phase behavior and detergency for oily soils. In this study, surfactant phase behavior was evaluated for hexadecane and motor oil as model oily soils. Producing microemulsions with these oils is particularly challenging because of their large hydrophobic character. To produce the desired phase behavior we included three surfactants with a wide range of hydrophilic/lipophilic character: alkyl diphenyl oxide disulfona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(93 citation statements)
references
References 36 publications
8
83
2
Order By: Relevance
“…The experimental results showed that all of the values of IFT between the excess oil and excess water fall in the same range of 10 -2 to 10 -1 mN/m. The IFT values obtained from the present study agree well with literature values (6,11), which show that a system with triolein generally has a higher IFT than those with other hydrocarbon oils (10 -4 to 10 -2 mN/m) due to the bulky molecular structure of triolein.…”
Section: Equilibrium Interfacial Tensionsupporting
confidence: 90%
See 2 more Smart Citations
“…The experimental results showed that all of the values of IFT between the excess oil and excess water fall in the same range of 10 -2 to 10 -1 mN/m. The IFT values obtained from the present study agree well with literature values (6,11), which show that a system with triolein generally has a higher IFT than those with other hydrocarbon oils (10 -4 to 10 -2 mN/m) due to the bulky molecular structure of triolein.…”
Section: Equilibrium Interfacial Tensionsupporting
confidence: 90%
“…Phase studies were carried out by first adding equal volumes of a surfactant solution and triolein into a flat-bottom screw-cap tube. The details of the phase behavior experiment were described in previous work (11). Both dynamic and equilibrium IFT of all prepared microemulsion systems were measured by a spinning drop tensiometer (model 500, University of Texas, Austin, TX).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aqueous surfactant solution and oil were added at a 1:1 v/v ratio to a series of 15-ml flat-bottomed screw-capped tubes 1,19,20,24 . Extended surfactant mixture systems were formulated at a high surfactant concentration of 4 wt with different concentrations of SMDNS from 0-1 and different NaCl concentrations in order to find a minimum hydrophilic linker and salinity for formation of a Winsor Type III microemulsion.…”
Section: Microemulsion Formationmentioning
confidence: 99%
“…The mixture was packed into a sample holder and pressed to form a disk. The spectra were recorded over a wave number range of 4000-400 cm 1 with 64 scans at a resolution of 4 cm 1 .…”
Section: Fourier Transform Infrared Ft-ir Spectroscopymentioning
confidence: 99%